The effect of five isometric exercises on glenohumeral translations in healthy subjects and patients with the hypermobility type of the ehlers-danlos syndrome (heds) or hypermobility spectrum disorder (hsd) with multidirectional shoulder instability: an observational study - Spanhove, Valentien; De Wandele, Inge; Kjær, Birgitte Hougs; Malfait, Fransiska; Vanderstukken, Fran; Cools, Ann (Physiotherapy, 2020)
To examine whether patients, diagnosed with the hypermobility type of the Ehlers-Danlos syndrome (hEDS) or Hypermobility Spectrum Disorder (HSD), with multidirectional shoulder instability (MDI) have increased humeral head translations compared to healthy controls and to describe the direction of the humeral translations during five exercises. Observational study. Ghent University Hospital. Twenty-seven female patients (aged mean (SD) 35 (13) years) with hEDS/HSD and MDI and 20 female healthy controls (aged 34 (11) years) participated in this study. The acromiohumeral (AHD) and humeralglenoid distance (HGD) were measured using ultrasound during five isometric exercises: shoulder external rotation, shoulder extension, shoulder flexion, elbow extension and holding a 2kg dumbbell. Ultrasound measures of the AHD and HGD. During isometric shoulder extension, elbow extension and dumbbell loading, patients had a significantly larger change in AHD compared to controls. In patients, the AHD was significantly smaller during isometric shoulder flexion, extension and elbow extension compared to the AHD measured in rest. By contrast, the AHD was significantly larger during isometric external rotation and dumbbell loading compared to the AHD measured in rest. Regarding the HGD, no significant differences between patients and controls were observed. However, significantly smaller HGD values were found in patients during isometric shoulder flexion compared to the HGD in rest. Isometric external rotation and holding a 2kg dumbbell caused an inferior translation in patients with hEDS/HSD and MDI, whereas isometric shoulder flexion and shoulder/elbow extension respectively led to an anterior-superior and superior translation.